Kualitas Kebijakan Publik dan Responsivitas Aparatur Terhadap Kepuasan Masyarakat di Kecamatan Campaka Kabupaten Cianjur - Hasmana, Heri; Nugraha, Anggi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze the influence of public policy quality and bureaucratic responsiveness on community satisfaction in public services in Campaka District, Cianjur Regency. The research employs a quantitative approach using a survey method and Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. The sample consists of 135 respondents, determined based on Hair’s approach, which suggests 5–10 times the number of indicators. The results indicate that public policy quality has a positive and significant effect on community satisfaction, with a coefficient value of 0.473, t-statistic of 4.760, and p-value of 0.000. Bureaucratic responsiveness also has a positive and significant effect, with a coefficient of 0.513, t-statistic of 5.114, and p-value of 0.000, and is identified as the more dominant variable. The R Square value of 0.960 shows that 96% of the variance in community satisfaction can be explained by these two variables. In addition, the Q² value of 0.653 indicates a very strong predictive capability of the model. These findings confirm that improving public policy quality and bureaucratic responsiveness simultaneously can optimally enhance community satisfaction.